Case Report of Unilateral Silent Sinus Syndrome with Variable Enophthalmos - Onur Gökmen; Altuğ Çetinkaya; Nilüfer Yeşilırmak; Fuat Büyüklü (Türk Oftalmoloji Dergisi)
A 35-year-old man applied to our clinic complaining that one of his eyes occasionally appeared smaller than the other for the last 6 months. The patient had no history of previous trauma or periorbital surgery. Ocular examination revealed 20/20 vision in both eyes and his pupillary and motility examinations were normal. The right eye showed 1mm hypoglobus and a deep superior sulcus. Considering possible silent sinus syndrome, CT scan was ordered and the diagnosis was established by visualizing an occlusion in the right osteomeatal aperture of the maxillary sinus with typical bending of the floor towards the sinus. The patient had undergone endoscopic sinus surgery through the right nasal meatus and the purulent material was drained through maxillary antrostomy. No intra-or postoperative complications were observed, and patient complaints and symptoms resolved immediately after the surgery. (Turk J Ophthalmol 2015; 45: 125-127